Importance of Integrated Simulation Approaches in Medical Education when Teaching Therapy Disciplines to Students of Medical Faculty - Yatsyshyn, Roman; Cherniuk, Nataliia; Drogomeretska, Oksana; Kuryliv, Halyna; Salyzhyn, Tetiana (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article is devoted to reviewing the main methods of practice-oriented teaching of medical students at the Department of Internal Medicine No. 1, Clinical Immunology and Allergology named after Academician Y. M. Neyko of Ivano-Frankivsk National Medical University (Ukraine). The significance of not only theoretical but also practical training of medical students in the conditions of blended learning is highlighted. The impact of new teaching methods on the level of future doctors' professionalism has been analyzed. Another important aspect of training is the introduction of simulation training, which allowed for obtaining a high level of knowledge without harming the patient. The article focuses on the role of the “virtual patient” in supervision, as this method, regardless of the form of study, allowed the student to be acquainted with a standardized patient, improve communication skills and choose the right method of diagnosis or treatment by the European guidelines. The article describes prospective systems for simulating clinical cases, which allow the creation of interactive training cases of various complexity levels depending on the goals set or the level of a specialist's training. The article presents the main online platforms for creating the most realistic cases with photographs of the affected body area and protocols of instrumental examinations, which allow you to reproduce the order of the doctor's actions and modify the intensity of the patient's condition if the prescription was incorrect. Moreover, the article highlights the positive impact of interactive teaching methods on student motivation and encouragement to deepen knowledge in a particular discipline, as an essential aspect is the discussion of examination results and prescription of therapy based on modern guidelines. It additionally outlines actions to be taken for ensuring efficient handling of new “virtual patient” cases and for inputting data on previously created clinical cases into the system. The article describes the main advantages of simulation-based teaching methods in comparison with traditional forms of teacher-student interaction. It is noted that training with the help of ”virtual patients” allows us to evaluate the acquired practical skills and competencies of future doctors.